2016
DOI: 10.1016/j.ypmed.2015.11.018
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of moderate-to-vigorous physical activity levels in elementary school physical education lessons

Abstract: MVPA levels during elementary school PE lessons do not meet the United States Centre for Disease Control and Prevention and the United Kingdom's Association of Physical Education recommendation (50% of lesson time), but is higher than estimated in the previous review (34.2%). Interventions to increase MVPA in PE lessons are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
161
4
16

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(191 citation statements)
references
References 38 publications
10
161
4
16
Order By: Relevance
“…It is also worth noting that a recent systematic review of the moderate-to-vigorous physical activity (MVPA) content of school PE globally suggested that a minority of time in PE classes was spent in MVPA. 14 …”
Section: Resultsmentioning
confidence: 99%
“…It is also worth noting that a recent systematic review of the moderate-to-vigorous physical activity (MVPA) content of school PE globally suggested that a minority of time in PE classes was spent in MVPA. 14 …”
Section: Resultsmentioning
confidence: 99%
“…The school setting is well established as a vehicle for physical activity interventions , however evidence indicates that a challenge exists in achieving the recommended 50-80% of time active during a standard physical education (PE) lesson (Hollis et al, 2016;Racette et al 2015;Association for Physical Education, 2015). Moreover, the tradition of competitive games 3 emphasising the importance of skill development, strategies and tactics has meant that health benefits have been viewed as a by-product of PE rather than a central goal (Kirk, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The whole school day and within that physical education (PE) are increasingly seen as important opportunities to accumulate PA 1–3. Paradoxically, even though school days including PE are more active than those that are not,3 PE is frequently identified as insufficiently active 4. Research papers and policy documents commonly use two objectives, advocated by organisations within the UK3 and the USA,5 to ascertain if PE is active enough (table 1).…”
mentioning
confidence: 99%